Negotiating Belonging through Food: Sambal, Commensality, and Insider-Outsider Relations in Puthut E.A.’s Sambal Keluarga - Putri , Helena Maharani; Tsabita, Abelia Nuha; Atikurrahman, Moh (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article examines how food mediates belonging in Puthut E.A.’s short story, Sambal Keluarga. This study asks how sambal and the breakfast ritual are constructed as a commensal code that produces collective family identity and how presence, absence, and mode of consuming sambal operate as a form of domestic hospitality that marks acceptance, deferred acceptance, or distance toward outsiders. This study employs a qualitative interpretive design combining close reading with qualitative content analysis. Primary data consist of meal scenes, naming practices, and dialogic moments in a short story, which are organized into thematic clusters and read through gastrocriticism, commensality theory, domestic hospitality, and symbolic boundary-making. This research finds that sambal functions not as a supplementary condiment but as the family’s central ritual object. Its recurrent presence at breakfast stabilizes affective continuity and validates collective identity, while its disappearance in the presence of guests signals the household’s strategic withholding of intimate access. Climactic scene involving Dian further shows that belonging is negotiated not only through access to the dish but also through conformity to the family’s taste code. This article lies in bringing commensality-centered gastrocriticism into conversation with Indonesian short fiction and demonstrating that ordinary culinary gestures can become precise literary mechanisms for staging insider-outsider relations.